ELAZIĞ SAĞLIK YÜKSEKOKULU ÖĞRENCİLERİNİN SAĞLIKLI YAŞAM BİÇİMİ DAVRANIŞLARI VE ETKİLEYEN FAKTÖRLER - CİHANGİROĞLU, ZUHAL (Fırat Üniveristesi, 2010)
Sağlıklı yaşam biçimi davranışları (SYBD); bireyin sağlıklı kalmak ve hastalıklardan korunmak için inandığı ve uyguladığı davranışların bütünü olarak tanımlanmaktadır. Bu araştırma Fırat Üniversitesi Elazığ Sağlık Yüksekokulu öğrencilerinin SYBD ve bunları etkileyen faktörlerin neler olduğunu belirlemek amacıyla yapılmıştır.Tanımlayıcı nitelikte olan bu çalışmanın evrenini F.Ü. Elazığ Sağlık Yüksekokulu'nda öğrenim gören öğrenciler (712 kişi) oluşturmuştur. Evrenin tümü araştırmaya dahil edilmiş, araştırma kapsamına alınan öğrencilerin 688'ine ulaşılmıştır. Araştırmanın verileri; birinci bölümde sosyo-demografik özellikler ile sağlıklı yaşam biçimi davranışlarını etkilediği düşünülen bazı faktörlerin değerlendirilmesi ile ilgili soruların, ikinci bölümde ise SYBD Ölçeği sorularının yer aldığı bir anketin direkt gözlem altında uygulanması ile toplanmıştır. Verilerin analizi t testi ve tek yönlü varyans analizi kullanılarak yapılmıştır.Araştırma kapsamına alınan öğrencilerin %74.3'ü kadın, %25.7'si erkek öğrenci olup, yaş ortalamaları 21.33 ? 1.85 (min:17, max:31)'dir. Öğrencilerin SYBD ölçeği genel ortalaması 121.75±18.86 puan (min:65, max:181) olarak saptanmıştır. Sağlığın geliştirilmesine katkıda bulunan davranışlar içerisinde en yüksek puan ortalamaları sırasıyla kendini gerçekleştirme, sağlık sorumluluğu ve kişilerarası destek boyutlarına, en düşük ortalama ise egzersiz alışkanlığına aittir. SYBD ölçeği ortalama puanının; üst sınıflarda okuyanlarda, sosyoekonomik düzeylerini orta ve yüksek olarak algılayanlarda, sigara içmeyenlerde, egzersiz yaptığını ifade edenlerde, kendi sağlık durumlarını orta ve iyi olarak değerlendirenlerde daha yüksek olduğu belirlenmiştir (P<0.05). Yaş arttıkça sağlık sorumluluğu ve kişilerarası destek puanlarının, kendi sosyoekonomik düzeyini olumlu yönde algılama derecesi yükseldikçe beslenme alışkanlığı, kendini gerçekleştirme, egzersiz alışkanlığı ve stres yönetimi puanlarının arttığı saptanmıştır (P<0.05).Sonuç olarak; Sağlık Yüksekokulu Öğrencilerinin sağlıklı yaşam biçimi davranışları orta düzeyde bulunmuştur. Sağlıklı yaşam biçimi davranışlarının öneminin kavranması ve günlük hayatta uygulanımı çabaları desteklenmelidir.Anahtar Kelimeler: Sağlık yüksekokulu öğrencileri, sağlığın geliştirilmesi, sağlıklı yaşam biçimi davranışları.

Healthy life style behaviours (HLSBs) are defined as all the activities which an individual believes in, and applies to maintain his/her healthy state , and also to protect him/herself from the deleterious effects of diseases. This investigation was conducted to exploit HLSBs of the students of Fırat University Elazığ High School of Health Sciences, and factors affecting their HLSBs.The context of this descriptive study involved the students (n= 712) educating in FU Elazığ High School of Health Sciences. All the participants were included in the investigation, however only 688 of them could be reached at the time of enrolment. The first part of the questionnaire of the investigation consisted of the documentation of sociodemographic characteristics, and answers to the questions related to evaluation of some factors thought to be influential on healthy life style behaviours. The second part constituted of data related to the collected responses given to the questions in the HLSB Scale under direct surveillance Data were analysed using t- test, and one-way analysis of variance.The students enrolled in the study consisted of females (74.3 %), and males (25.7 %) with a mean age of 21.33±1.85 years (17-31 years). Mean HLSB Scale score of the students was estimated to be 121.75±18.86 points (65-181 points) The maximal mean points contributing to the development of healthy life style were related to self-realization, responsibility for self-health, and interindividual supportive measures in decreasing order, while habitual exercise accounted for the lowest means. Mean scores in HLSB scale were determined to be higher in senior class students, those conceiving their socioeconomic status as being at a moderate or higher levels, non-smokers, students who are statedly on routine exercise programs, and individuals whose self-assessment of their state of health as being of moderate and improved levels (P<0.05). It was found that with increasing age, points assigned for responsibility for his/her wellbeing, interpersonal support increased, while favourable perception of one?s socioeconomic status enhanced points allocated to dietary habits, self-realization, habitual exercise, and stress management (P<0.05).In conclusion, the healthy life style behaviours of the students of High School of Health Sciences are found to be of moderate level. The significance of healthy life style behaviours should be recognized, and and attempts to use them during activities of daily life should be encouraged.Key words: Students of High School of Health Sciences, development of health, healthy life style behaviours.
Healthy life style behaviours of the students of Elazig High School of health sciences and related influencing factors
Keywords: Halk Sağlığı